2008
DOI: 10.1124/dmd.107.019125
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Multidrug Resistance-Associated Protein 2 (Abcc2) in Molecular Weight-Dependent Biliary Excretion of β-Lactam Antibiotics

Abstract: ABSTRACT:In the present study, we attempted to identify the membrane permeation process(es) primarily involved in the molecular-weightdependent biliary excretion of ␤-lactam antibiotics. A search of the literature indicated that the molecular weight threshold operates mainly in the transport process across bile canalicular membranes. We confirmed that biliary clearance of the model biliaryexcretion-type cephalosporin cefoperazone was reduced to 10% of the control in Eisai hyperbilirubinemic rats, which are gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…In the current study, we used membrane vesicles prepared from insect Sf9 cells expressing ABC transporters. Because we have shown that Mrp2 transport activity in the same system corresponded well with its in vivo function (Kato et al, 2008), it was thought that these results reflect physiological function of these transports. Indeed, results obtained from Bcrp-expressing vesicles are consistent with the findings in Bcrp(Ϫ/Ϫ) mice (Nezasa et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the current study, we used membrane vesicles prepared from insect Sf9 cells expressing ABC transporters. Because we have shown that Mrp2 transport activity in the same system corresponded well with its in vivo function (Kato et al, 2008), it was thought that these results reflect physiological function of these transports. Indeed, results obtained from Bcrp-expressing vesicles are consistent with the findings in Bcrp(Ϫ/Ϫ) mice (Nezasa et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…MRP2 plays an essential role in regulation of the serum bilirubin level by eliminating its conjugate from the liver, because a genetic defect of MRP2 in humans leads to familial conjugated hyperbilirubinemia, known as Dubin-Johnson syndrome (Kartenbeck et al, 1996;Paulusma et al, 1997). In addition, MRP2 mediates efflux transport into bile of many structurally diverse xenobiotics and anticancer drugs in either intact or conjugated forms (Kato et al, 2008). We have shown that MRP2 plays an important role in the hepatobiliary secretion of drugs by using SCRHs (Fukuda et al, 2008(Fukuda et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Because Bcrp protein expression increased during culture, in contrast to the decrease in Mrp2 and bile salt export pump expression (Li et al, 2010), intrinsic biliary clearance for rosuvastatin is relatively higher than that of other compounds in SCRH. Meanwhile, it was reported that Mrp2 mainly contributes to biliary secretion of pravastatin, angiotensin receptor blockers (valsartan and olmesartan), and ␤-lactam antibiotics (cefoperazone and cefpiramide) (Muraoka et al, 1995;Sasaki et al, 2004;Takayanagi et al, 2005;Yamashiro et al, 2006;Kato et al, 2008). Because the main contributor that excreted rosuvastatin into bile was different from that for the other compounds, a deviation of rosuvastatin from the correlation among these compounds would be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Because the main contributor that excreted rosuvastatin into bile was different from that for the other compounds, a deviation of rosuvastatin from the correlation among these compounds would be observed. Meanwhile, it was reported that cefmetazole was not a substrate of Mrp2 and Bcrp (Kato et al, 2008). Although the primary transporter for biliary excretion of cefmetazole is unknown, it may be possible that the activity change of the main contributors for biliary excretion of cefmetazole caused the deviation of cefmetazole from the correlation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reasons behind the molecular mass threshold are not well understood. Kato et al (2008) studied the substrate affinity of the cephalosporins for MRP2 and BCRP and suggested involvement of efflux pumps in molecular mass-dependent BE of ␤-lactam antibiotics in rats. Because of the broad substrate specificity of the canalicular efflux transporters [P-glycoprotein (P-gp), BCRP, and MRP2], we hypothesized that substrate specificity of sinusoidal uptake transporters, particularly OATPs, defines the molecular mass threshold and the general physicochemical space of BE.…”
Section: Introductionmentioning
confidence: 99%